An efficient chaos based image encryption algorithm using enhanced thorp shuffle and chaotic convolution function - Kumar, C. Madan; Vidhya, R.; Brindha, M. (Applied intelligence (Dordrecht, Netherlands), 2022)
A Unique chaotic image encryption on the basis of Enhanced Thorp shuffle and Zig-zag Scan based Convolution (ETS-ZSC) is proposed in this paper. A one-dimensional chaotic map is utilized for both shuffling the plain image and producing the critical grid for the convolution activity. The substitution operation is performed in two ways: forward substitution and reverse substitution with zigzag scan. The original seed of the logistic map is created from the hyper chaotic system by matching with the plain image to overcome the differential attacks. The security analyzes are held for the proposed method to prove safe against the chosen plain text/known plain text attack. From the simulations results, it is observed that the proposed methodology is having enough high key sensitivity, key space, good randomness, and equal sharing of pixels in cipher image.